Sector-level economic modeling as a tool in evaluating greenhouse gas mitigation options - Lehtonen, Heikki (Taylor & Francis, 2013)
An agricultural sector model is used in simulating agricultural markets under changing policies and markets, implying changes in regional production structure and land use. Given the direct farm-level costs of implementing specific abatement options as inputs, the sector model shows their likely impacts on agricultural production and land use in different regions. Most importantly, the sector-level model also includes indirect effects through product markets, i.e. changes in the balance of supply and demand. The sector model includes the endogenous structural development of agriculture, i.e. farm size growth and changes in production allocation in different regions. Hence, the dynamic sector model, while including specific descriptions of agricultural policies and markets, shows a consistent overall picture of the agricultural production development impacted by the GHG mitigation measures. The approach provides a unifying framework for farm-level analysis at multiple regions and scales.
Keywords: Maatalous - yleistä, maatalousekonomia,maatalousneuvonta, maaseudun kehittäminen; abatement costs; spatial production structure; structural change; maatalouspolitiikka; kasvihuoneilmiö; agricultural economics; agricultural policy; maatalousekonomia; maatalouspolitiikka; kasvihuonekaasut